English ethnicity and culture in North America - Gleeson, David T. (The University of South Carolina Press, 2017)
"As Van Vugt's analysis of English immigrants in the United States is an appropriate place to begin this collection, so Sutton's essay is a fitting one to conclude it. Sutton confirms in many ways a belief shared by all of us involved in this project: that as with other ethnicities in North America, English culture did not disappear into a larger mainstream but instead was adapted, merged, and transformed into something hybrid. St. Patrick's Day, for example, began in North America as an exclusive ethnic festival for Irish immigrants, but it has been transformed into something that is as much, if not more, American as it is Irish. Preserved by ethnic associations for their future "hyphenated" generations, this idea of a symbiotic assimilation of immigrant cultures in the U.S. and Canadian mainstreams is accepted by scholars. We believe that this applies to English literature, pageantry, commemorations, cricket, and much more, and we hope that this initial foray will encourage others to pursue the numerous other sources of English ethnicity in the United States and Canada and how they were transformed on the western side of the Atlantic" ...